Workplace Loneliness, Work-Family Conflict, dan Job Stress terhadap Turnover Intention pada Karyawan Perempuan di Kabupaten Mamuju - Anisa, Anisa; Aqil, Muhammad; Ferils, Muh.; Dahri, Nur Wahyunianti (Jurnal E-Bis, 2025)
An employee's intention to leave their job is known as turnover intention, and it can negatively affect the company if it is not handled appropriately. This study’s objective is to determine the effect of workplace loneliness, work-family conflict, and job stress on turnover intention among female employees in Mamuju Regency. This research uses associative quantitative methods with incidental sampling techniques and involves 100 respondents as samples. The results obtained (1) Workplace loneliness has a positive and significant effect on turnover intention; (2) Work-family conflict has a positive and significant effect on turnover intention; (3) Job Stress has a positive and significant effect on turnover intention; (4) Workplace loneliness, work-family conflict, and job stress simultaneously have a significant effect on turnover intention with a contribution of 74.9 percent, which is included in the strong category; (5) Job Stress has the most dominant influence on turnover intention.